Education, outreach activities and training of human resources to promote biological weed control in Argentina - Jiménez, Nadia Lis; Faltlhauser, Ana Claudia; Righetti, Tomás; Franceschini, Celeste; Cécere, Carla; Daddario, Facundo; Villamil, Soledad; Fernández Souto, Adriana Beatriz; Hill, Martin; Mc Kay, Fernando; Sosa, Alejandro Joaquín (Fundación para el Estudio de Especies Invasivas (FuEDEI), 2023)
Public awareness is an important component to prevent introduction or resurgence of invasive alien species (IAS). A positive public perception of biological control is essential to support and demand that policy makers implement it in management programmes. Public visibility and research on weed biological control in Argentina have grown in the last decade, mainly due to a series of educational and outreach activities led by research teams from FuEDEI, CONICET, and national universities. Since then, ~6,100 people have participated in outreach activities and environmental education on invasive plants and biological control through our participation in community and science fairs. We provided training courses to 350 school teachers and gave talks about knowledge and perception of IAS to ~1,100 school students. We teach courses on biological control of invasive plants and arthropods every year that have reached, to date, 1,210 undergraduate and graduate students from eight public universities in the country. Furthermore, 30 PhD students and young researchers were incorporated in the national scientific system to investigate different aspects of biological control (e.g., genetics, ecology, social science). A free gamified application called “Especies” was developed for teachers and students from secondary schools in Argentina as a friendly learning tool to study the importance of IAS and their management through a United Nations Development Program. We also initiated the implementation of the biological control programme of water hyacinth (Pontederia crassipes) in a small lake in San Vicente (Buenos Aires province). Soon after, it became an educational project of the city's agrarian secondary school where students and teachers mass-reared and released host-specific insects to control the water hyacinth invasion. Over time, water hyacinth biological control gained visibility and support among the community, which gave us the opportunity to teach and award a technical diploma in aquatic weed management to 30 people. We are also involved in training and counseling for several national and municipal level government agencies (e.g., FuEDEI provided training courses in the Agriculture Ministry), and international initiatives. All these initiatives could contribute to increasing public awareness about the importance of IAS, raising the profile of weed biological control, and promoting new research opportunities for further growth in Argentina.
Trabajo presentado en el XVI International Symposium on Biological Control of Weeds, realizado en Puerto Iguazú, Argentina, del 7 al 12 de mayo de 2023 organizado por International Organisation for Biological Control (IOBC)
Keywords: Ciencias sociales::Ciencias de la educación